Role of extracellular vesicles in sarcopenia associated to chronic liver diseases. (March 2023) - Barberi, L.; Porcu, C.; Boccia, C.; di Cola, S.; Fonte, S.; Ridola, L.; Musarò, A.; Merli, M.
Abstract : Introduction: A loss of muscle mass and strength, referred as sarcopenia, is a condition highly prevalent in patients with chronic liver disease. Pathogenesis of sarcopenia is multifactorial and mainly results from an imbalance between protein synthesis and degradation. Mechanisms underlying sarcopenia in liver disease are still not completely understood as the mediators of the liver-muscle axis have not yet been identified. Aim: Given the close metabolic interplay between skeletal muscle and liver and the emerging role of extracellular vesicles (EVs) in mediating intercellular communication, we evaluated whether circulating EVs in liver disease could vehicle to skeletal muscle microRNAs able to induce or contribute to sarcopenia. Materials and Methods: Primary human myoblasts were exposed to serum EVs from healthy (H-EVs; n=9) and cirrhotic individuals (C-EVs; n=13) and analysed for their ability to differentiate and for the expression of markers of protein synthesis and degradation. Moreover, expression levels of microRNAs involved both in liver disease and in muscle development were examined in C-EVs and compared to those of H-EVs. Results and Conclusion: We demonstrated that circulating EVs were efficiently internalized by skeletal muscle cells and that C-EVs were able to cause in vitro muscle atrophy, inducing a decrease in muscle differentiation, highlighted by a reduced fusion index and a downregulation of Myosin protein amount ( p <0.05) and an increase in protein degradation, revealed by an upregulation of Murf-1 and Atrogin-1 mRNA expression levels ( p <0.05), compared to H-EVs.Furthermore, we showed that C-EVs exhibited significant higher expression levels of microRNAs, such as miR-223, –133a, -29a, -128a, -21, and -199a-3p, targeting the two most important signaling pathways in muscle tissue: the TGF-β/myostatin/BMP and PI3K/AKT/mTOR pathways, regulating protein and synthesis and degradation respectively. Therefore, circulating EVs could be key players of the liver-muscle axis in sarcopenia associated to liver disease.